The Effect of Milkfish Stomach Waste Compost on Cayenne Pepper Growth (Capsicum frutescens L.) - Nuraeni Nuraeni; Dadan Rosana (Jurnal Ilmu Pertanian Indonesia, 2025)
Cayenne pepper (Capsicum frutescens L.) is a high-value horticultural commodity with various benefits, ranging from food ingredients to medicinal purposes. However, cultivation still faces challenges, such as dependency on chemical fertilizers, which can harm the environment. As a solution, organic fertilizer derived from milkfish stomach waste has the potential to be utilized due to its rich nutrient content and environmentally friendly properties. This study aimed to examine the effect of varying amounts of milkfish stomach waste compost on the growth of cayenne pepper plants. The research employed a Completely Randomized Design with five compost mass treatments (0, 200, 300, 400, and 500 g) applied to cayenne pepper plants. The observed parameters included the plant height and leaf count. The results indicated that the compost mass significantly affected the growth of cayenne pepper plants. Treatment with 500 g of compost yielded the best results, marked by the highest average increase in plant height and leaf count compared to other treatments. This study demonstrates that milkfish stomach waste has excellent potential as a raw material for organic fertilizers to support the growth of horticultural crops in the future. Keywords: cayenne pepper, compost, milkfish waste, organic fertilizer, plant growth